Assessment of the distribution system for oral contraceptives and devices in selected rural health units of Cavite - Isla, Johanna Faith Patricia S.​; Pamittan, Krystal Gayle A.​; Rivera, Neil Osbert C.​
The Responsible Parenthood and Reproductive Health Act of 2012 mandates the Department of Health to allow free access to the information, products, and services for reproductive health. DOH made this happen by implementing a Family Planning Project, where the supplies of contraceptives were being delivered from the warehouse of the department to the RHUs and LGUs of the municipalities for distribution. A good distribution system requires an enough and stable supply of contraceptives and promotes to use these supplies in the most efficient way. However, reports have been raised regarding stock out of supplies for contraceptives. The study aims to evaluate the distribution system for oral contraceptives and devices in selected RHUs through describing the current distribution system based on the WHO Handbook of Supply Management at First-Level Health Care Facilities checklist and determining if these supplies are reaching the patients. The assessment for the RHU was done though interview and observation using checklist adapted from the WHO. Parallel to that, patients were interviewed on the use of contraceptives and information provided by the RHU personnel during dispensing. The RHUs were compliant with the WHO standard for medicines management of drugs at health center level. The problem with the system heavily stems on the insufficient budget to ensure quarterly delivery of supplies. The interview with the patients suggests that there was an efficient information dissemination, however, only 56.36% of the patients actually availed the contraceptives from the RHU. It is recommended for RHUs to strengthen the importance of patient counseling, hold educational campaigns to inform and empower the patients about the use of contraceptives, maintain the well-managed distribution system by using the WHO checklist and by observing proper storage for the contraceptives.